Learnings about the complexity of extracellular tau aid development of a blood‐based screen for Alzheimer's disease. Issue 3 (9th November 2018) - Chen, Zhicheng; Mengel, David; Keshavan, Ashvini; Rissman, Robert A.; Billinton, Andrew; Perkinton, Michael; Percival‐Alwyn, Jennifer; Schultz, Aaron; Properzi, Michael; Johnson, Keith; Selkoe, Dennis J.; Sperling, Reisa A.; et al.
Abstract: Introduction: The tau protein plays a central role in Alzheimer's disease (AD), and there is huge interest in measuring tau in blood and cerebrospinal fluid (CSF). Methods: We developed a set of immunoassays to measure tau in specimens from humans diagnosed based on current best clinical and CSF biomarker criteria. Results: In CSF, mid‐region‐ and N‐terminal‐detected tau predominated and rose in disease. In plasma, an N‐terminal assay (NT1) detected elevated levels of tau in AD and AD‐mild cognitive impairment (MCI). Plasma NT1 measurements separated controls from AD‐MCI (area under the curve [AUC] = 0.88) and AD (AUC = 0.96) in a discovery cohort and in a Validation Cohort (with AUCs = 0.79 and 0.75, respectively). Discussion: The forms of tau in CSF and plasma are distinct, but in each specimen type, the levels of certain fragments are increased in AD. Measurement of plasma NT1 tau should be aggressively pursued as a potential blood‐based screening test for AD/AD‐MCI.